‘These Off-beat “Crazy Kids and Gals”’: Jazz in Ireland, 1918–1960 - Evans, Damian (Journal of the Society for Musicology in Ireland, 2019)
This paper conducts a historical overview of jazz in Ireland, with a focus on the Dublin jazz scene from 1918 to 1960. Using archival resources, it looks at black and black-influenced music, minstrelsy and blackface before examining the arrival and reception of early jazz in what was then part of the United Kingdom of Great Britain and Ireland. It traces the changing nature of the Dublin jazz scene, covering topics such as jazz as dance music, the anti-jazz movement and the development of the dominant narrative of jazz as art-form that continues to this day. This paper also documents the shifting reception of jazz in Ireland from a threatening foreign music through to a music that has served the purposes of both entertainment and art. It makes a case for the Irish jazz narrative to include the activities of amateur musicians, dance band musicians and others, arguing that their involvement with jazz went beyond a casual interest, establishing an active community of practice that constituted an early Irish jazz scene.